NEW DATA ON THE GENUS SYRPHUS FABRICIUS, 1775 (DIPTERA: SYRPHIDAE) FROM THE BALKAN PENINSULA INCLUDING THE FIRST RECORD OF SYRPHUS NITRIDIFRONS BECKER, 1921 (Acta Entomologica Serbica, 2010)
Four species of the genus Syrphus Fabricius, 1775 have been recorded in the Balkan Peninsula: S. nitidifrons Becker, 1921, S. ribesii (Linnaeus, 1758), S. torvus Osten Sacken, 1875 and S. vitripennis Meigen, 1822. The first documented record of S. nitidifrons from the Balkan Peninsula is provided, as well as keys for both males and females, lists of material examined and distribution maps for each Balkan Syrphus species. Syrphus torvus is new to Croatia. All the studied taxa are widespread throughout the Balkans, except S. nitidifrons, limited to a few mountain localities: Kopaonik Mountain (Serbia), Jahorina Mountain (Bosnia and Herzegovina) and Durmitor Mountain (Montenegro). The need for conservation of S. nitidifrons is remarked.